An automated method measures variability in P-glycoprotein and ABCG2 densities across brain regions and brain matter. Issue 6 (June 2017) - Kannan, Pavitra; Schain, Martin; Kretzschmar, Warren W; Weidner, Lora; Mitsios, Nicholas; Gulyás, Balázs; Blom, Hans; Gottesman, Michael M; Innis, Robert B; Hall, Matthew D; Mulder, Jan
Changes in P-glycoprotein and ABCG2 densities may play a role in amyloid-beta accumulation in Alzheimer's disease. However, previous studies report conflicting results from different brain regions, without correcting for changes in vessel density. We developed an automated method to measure transporter density exclusively within the vascular space, thereby correcting for vessel density. We then examined variability in transporter density across brain regions, matter, and disease using two cohorts of post-mortem brains from Alzheimer's disease patients and age-matched controls. Changes in transporter density were also investigated in capillaries near plaques and on the mRNA level. P-glycoprotein density varied with brain region and matter, whereas ABCG2 density varied with brain matter. In temporal cortex, P-glycoprotein density was 53% lower in Alzheimer's disease samples than in controls, and was reduced by 35% in capillaries near plaque deposits within Alzheimer's disease samples. ABCG2 density was unaffected in Alzheimer's disease. No differences were detected at the transcript level. Our study indicates that region-specific changes in transporter densities can occur globally and locally near amyloid-beta deposits in Alzheimer's disease, providing an explanation for conflicting results in the literature. When differences in region and matter are accounted for, changes in density can be reproducibly measured using our automated method.